Analiza porównawcza dwóch przykładów świata VUCA: osoby chorujące na stwardnienie rozsiane i osoby doświadczające pandemii COVID-19 - Trojanowska, Milena (Życie z niepełnosprawnością w świecie VUCA, 2022)
The purpose of the paper is to provide a comparative analysis of two examples of the VUCA world. The first is the world of people living with multiple sclerosis (MS), a chronic disease of the immune system. The second is the world of individuals experiencing the COVID-19 pandemic. The analysis revealed the positive and negative consequences of operating in a world characterized by volatility, uncertainty, complexity, and ambiguity. Benefits include psychological growth, the ability to negotiate, reconstruct and reflect on socially established meanings. Negative aspects include isolation, depressive disorders and depression, anxiety and fear, abandonment of work activities, or lack of access to a source of income. The interpretive approach of qualitative research was used in the conducting of the study. The results indicate that the VUCA world concept is universal and can be used in many research fields.